2019
DOI: 10.1186/s12890-019-1029-x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells prior to initial treatment is an important prognostic factor of survival in non-small cell lung cancer: a meta-analysis and system review

Abstract: BackgroundOur study aimed to verify the prognostic value of circulating tumor cells (CTCs) prior to initial treatment on survival of non-small cell lung cancer (NSCLC) by using meta-analysis and system review of published studies.Materials and methodsThe PubMed, EMBASE and Cochrane Library were searched, respectively, to identify all studies that addressed the issues of CTCs prior to initial treatment and progression-free survival (PFS) and overall survival (OS). Finally, ten citations were included for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
13
1
Order By: Relevance
“…A number of meta-analyses have suggested that having high CTCs prior to treatment is a prognostic factor of survival [ 44 ] and have identified the use of circulating tumor DNA (ctDNA) and CTCs as biomarkers for the detection of mutation status in NSCLC [ 45 , 46 , 47 ], while presence of CTCs also seems to indicate poor prognosis in SCLC [ 48 ].…”
Section: Clinical Relevance Of the Presence Of Ctcs In Lung Cancermentioning
confidence: 99%
“…A number of meta-analyses have suggested that having high CTCs prior to treatment is a prognostic factor of survival [ 44 ] and have identified the use of circulating tumor DNA (ctDNA) and CTCs as biomarkers for the detection of mutation status in NSCLC [ 45 , 46 , 47 ], while presence of CTCs also seems to indicate poor prognosis in SCLC [ 48 ].…”
Section: Clinical Relevance Of the Presence Of Ctcs In Lung Cancermentioning
confidence: 99%
“…Numerous studies have reported that CTCs have significant prognostic value in various solid tumors, including breast cancer, colorectal cancer, head and neck cancer, esophageal cancer, and lung cancer. 9 - 14 According to previously published studies, it is reported that the concentration of CTCs in SCLC is the highest among all solid tumors, which can mirror the high metastatic tendency of SCLC. 1 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Non-small-cell lung cancer (NSCLC) acts as the major subtype of lung cancer approximately 85% 1 , 2 . NSCLC is the most common malignancy and could give rise to tens of millions of death cases worldwide 3 .…”
Section: Introductionmentioning
confidence: 99%